Obstetric performance and pelvic dystopia (retrospective study in 100 patients) - Cervantes Begazo, René (2015)
Among the causes or conditions of the pelvic dystopias and especially genital prolapse and its different varieties, the obstetric trauma as one of the most important mentioned. The damage to the levator ani muscles and distention and fascia injury and support elements that form the pelvic floor and hold the uterus, bladder and rectum in its anatomical relations, determine the abnormal position and falling structures pelvic and therefore different varieties of dystopia.